At the beach : the parts of a day - Proctor, Alice, 1967- (Pleasantville, NY : Weekly Reader, 2008)
Photographs and simple text introduces young readers to time and the five main parts of the day.
All in a day -- My day at the beach -- Morning at the beach -- Noon at the beach -- Afternoon at the beach -- Almost time to go home -- At home in the evening -- Nighttime -- Time facts -- Time to remember.
Previously published: Great Britain : ticktock Media Ltd., 2007.
1.4
K-3
Keywords: Beaches -- Juvenile literature; Days -- Juvenile literature; Time -- Juvenile literature; Beaches; Days; Time; Beaches; Days; Time